2013
DOI: 10.3855/jidc.2748
|View full text |Cite
|
Sign up to set email alerts
|

Viral load of human papillomavirus in women with normal and abnormal cervical cytology in Kuwait

Abstract: The findings suggest that, in the absence of a proper screening programme in Kuwait, quantification of HPV viral load could be considered as a surrogate virology test to identify women with abnormal cytology. Further population-based prospective studies are needed to include more women with high-grade and invasive carcinoma reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…High risk HPVs in the current study were observed in 16.1% of NILM Pap smears, which fall near the lower third of the worldwide (0%-60%) range rates (Clifford et al, 2005;Bosch et al, 2008;Pity et al, 2012;Al-Awadhi et al, 2013;Pity 2013;Faik et al, 2015;Donkoh, 2016). Unmasking the burden of HR-HPV in NILM smears is notorious because of their effective ability to transform normal cell phenotype into a malignant one.…”
Section: Mixed Hpv Infectionsupporting
confidence: 47%
“…High risk HPVs in the current study were observed in 16.1% of NILM Pap smears, which fall near the lower third of the worldwide (0%-60%) range rates (Clifford et al, 2005;Bosch et al, 2008;Pity et al, 2012;Al-Awadhi et al, 2013;Pity 2013;Faik et al, 2015;Donkoh, 2016). Unmasking the burden of HR-HPV in NILM smears is notorious because of their effective ability to transform normal cell phenotype into a malignant one.…”
Section: Mixed Hpv Infectionsupporting
confidence: 47%
“…Although higher viral loads may result from an increased rate of viral replication and may sustain viral persistence [Yoshida et al, 2008], this study demonstrated that the viral loads of HPV 52 and 16 at entry were not associated with the degree of cytologic abnormalities, supporting the idea that HPV DNA load seems to predict the risk of developing cervical carcinoma before any cytological alterations are visible . This result is not in accordance with previous studies [Carcopino et al, 2012;Al-Awadhi et al, 2013], and this discrepancy may reflect the small sample size used in the current study. Further studies using a greater number of patients are required to establish the reason for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In this general screening, we found only a few LGSIL and HGSIL cases. As is the situation in Kuwait, viral load and higher numbers of samples might reveal a situation with a different picture [27]. We are in the process of starting a prospective study to measure E6/E7 mRNA [28] in fresh cervical specimens and then follow those positive cases to explore the progress to cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%